Evaluation of SIMESON, a training program to improve access to quality health care for pregnant women and newborn in different healthcare facilities of northern Bangladesh. Issue 1 (16th November 2021) - Das, Rina; Farzana, Fahmida Dil; Sultana, Zakia; Mukherji, Kallol; Baayo, Adnan; Sultana, Marufa; Ali, Nausad; Chisti, Mohammod Jobayer; Sarker, Shafiqul Alam; Ahmed, Tahmeed; Faruque, ASG
Abstract: Aim: The study aims to explore the current knowledge and skills of healthcare providers already trained by SIMESON (simulation for essential skills for obstetrical and neonatal care), in reviewing perinatal health situations including current status of healthcare facilities and cost estimation. Design: It was an observational study. Methods: Cost estimation following both quantitative and qualitative approaches was also attempted. Result: Knowledge and skills of 88 healthcare providers about the provision of normal delivery and immediate postpartum care, management of postpartum haemorrhage (PPH), retained placenta and use of bag and mask ventilation to help a baby breathe were found to be considerably strengthened following SIMESON training. During the 6 months after training, there were 477 PPH cases managed successfully with only one death; neonatal deaths observed were 6.6/1, 000 live births; twice the number of facility deliveries; and 80% use rate of Ambu bag for helping baby breathe. The estimated cost per trainee was 395.68 USD, and 5.85 USD per beneficiary.